2015
DOI: 10.1139/cjpp-2014-0262
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of baicalin on LPS-induced injury in intestinal epithelial cells and intercellular tight junctions

Abstract: Baicalin has the capacity to protect IEC-6 cells and the intercellular tight junctions from LPS-induced injury. The mechanisms may be associated with inhibiting the production of inflammatory cytokines, and up-regulating the mRNA and protein expression of ZO-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
4
30
0
Order By: Relevance
“…ZO-1 was the first TJ protein to be discovered (45) and is directly associated with occludin, serving an important role in regulating TJ barrier function (46). It has been reported that LPS is able to decrease the expression of ZO-1 and occludin (47), which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 94%
“…ZO-1 was the first TJ protein to be discovered (45) and is directly associated with occludin, serving an important role in regulating TJ barrier function (46). It has been reported that LPS is able to decrease the expression of ZO-1 and occludin (47), which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 94%
“…The failure of intestinal barrier function induced with LPS resulted in an increase in mucosal permeability, which was hypothesized to be a major promoter of bacterial translocation and inflammatory cytokines release[30,31]. IL-6 and TNF-α are the critical cytokines involved in inflammation, and bifidobacterium is regarded as a common treatment strategy for information-related diseases, including NEC [22,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…16) Orally administered baicalin inhibits the expression of TNF-α in mice injected with LPS via regulating the activation of the transcription factor nuclear factor-kappaB (NF-κB). 39) Moreover, high levels of TNF-α following LPS stimulation were associated with severe loss of ZO-1 in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…16) Briefly, cells were grown in complete Dulbecco's modified Eagle's medium (DMEM; Hyclone) at 37°C in 5% CO 2 and were then subcultured after digestion with 0.25% trypsin in phosphate buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation